2017
DOI: 10.1083/jcb.201707161
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the synaptonemal complex protein SYP-1 promotes meiotic chromosome segregation

Abstract: Sato-Carlton et al. show that the partitioning of Caenorhabditis elegans chromosomes into two domains that differentially mediate separation in meiosis I and II requires phosphorylation of the synaptonemal complex protein SYP-1, which in turn promotes Polo-like kinase 2 localization to the synaptonemal complex.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 68 publications
4
52
0
Order By: Relevance
“…While we were preparing this paper, phosphorylation of SYP-1 with a role in meiosis progression was described ( Sato-Carlton et al., 2018 ). This prompted us to test if this modification is altered in our strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While we were preparing this paper, phosphorylation of SYP-1 with a role in meiosis progression was described ( Sato-Carlton et al., 2018 ). This prompted us to test if this modification is altered in our strains.…”
Section: Resultsmentioning
confidence: 99%
“…The SC is a dynamic structure that operates during meiosis to ensure the formation of crossovers while at the same time limiting their numbers ( Colaiácovo et al., 2003 , Saito and Colaiácovo, 2017 ). Phosphorylation of SC components has been recently reported to influence changes in SC dynamics and meiotic recombination during unperturbed meiosis ( Nadarajan et al., 2017 , Sato-Carlton et al., 2018 ). Intriguingly, a previous study reported that the SC undergoes localized disassembly during the repair of IR-induced DSBs to favor rapid repair through the sister chromatid as template ( Couteau and Zetka, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During late meiotic prophase, SC components were found to remain associated with chromosome subdomains in diverse organisms ( Bisig et al, 2012 ; Gladstone et al, 2009 ; Nabeshima et al, 2005 ; Newnham et al, 2010 ; Qiao et al, 2012 ; Takeo et al, 2011 ); however, the molecular consequences for such retention are not clear. In Caenorhabditis elegans , although asymmetric SC disassembly accompanies chromosome remodeling and the establishment of bivalent asymmetry required for their accurate segregation ( de Carvalho et al, 2008 ; Martinez-Perez et al, 2008 ; Sato-Carlton et al, 2018 ; Tzur et al, 2012 ), the requirement for the maintenance of SC components during this process is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Those involved in histone modifications (Sasaki et al, 2008; Xu et al, 2009; Kota et al, 2010; Greer et al, 2011; Yelina et al, 2014; Székvölyi et al, 2015; Termolino et al, 2016) are frequently associated with changes in transcription, which is one of the reasons why we expected to detect larger changes in the meiotic transcription profile. However, several PTM are also involved in the modification of other meiotic proteins (Watanabe et al, 1997; Carballo et al, 2008; Fukuda et al, 2012; Sato-Carlton et al, 2017). Most of these meiotic PTMs have been reported in yeast and mammals, where synaptonemal complex formation and recombination are regulated through PTMs such as ubiquitination and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%